Raman Scattering Study on the Influence of E-Beam Bombardment on Si Electron Lens - Lee, Geon-Woo; Lee, Young-Bok; Baek, Dong-Hyun; Kim, Jung-Gon; Kim, Ho-Seob (Molecules (Basel, Switzerland), 2021)
Microcolumns have a stacked structure composed of an electron emitter, electron lens (source lens), einzel lens, and a deflector manufactured using a micro electro-mechanical system process. The electrons emitted from the tungsten field emitter mostly pass through the aperture holes. However, other electrons fail to pass through because of collisions around the aperture hole. We used Raman scattering measurements and X-ray photoelectron spectroscopy analyses to investigate the influence of electron beam bombardment on a Si electron lens irradiated by acceleration voltages of 0, 20, and 30 keV. We confirmed that the crystallinity was degraded, and carbon-related contamination was detected at the surface and edge of the aperture hole of the Si electron lens after electron bombardment for 24 h. Carbon-related contamination on the surface of the Si electron lens was verified by analyzing the Raman spectra of the carbon-deposited Si substrate using DC sputtering and a carbon rod sample. We report the crystallinity and the origin of the carbon-related contamination of electron Si lenses after electron beam bombardment by non-destructive Raman scattering and XPS analysis methods.